Gap junction structures. I. Correlated electron microscopy and x-ray diffraction (The Rockefeller University Press, 1977)
X-ray crystallographic methods and electron microscope image analysis have been used to correlate the structure and the chemical composition of gap junction plaques isolated intact from mouse liver. The requirement that the interpretations of X-ray, electron microscope, and chemical measurements be consistent reduces the uncertainties inherent in the separate observations and leads to a unified picture of the gap junction structures. Gap junctions are built up of units called connexons that are hexagonally arrayed in the pair of connected cell membranes. X-ray diffraction and electron microscope measurements show that the lattice constant of this array varies from about 80 to 90 A. Analysis of electron micrographs of negatively stained gap junctions shows that there is significant short range disorder in the junction lattice. even though the long range order of the array is remarkably regular. Analysis of the disorder provides information about the nature of the intermolecular forces that hold the array together.